Potensi Trichoderma spp. Pada Pengomposan Sampah Organik sebagai Media Tumbuh dalam Mendukung Daya Hidup Semai Tusam (Pinus merkusii. et de Vries) - M. Marhiansyah; SM. Widyastuti (Jurnal Sagu, 2007)
The experiment purpose was to evaluate the effect of Trichoderma spp. Substitution during composition process on the quality of resulted compos. Compos made from organic debris as the main component and fresh cow dung decomposer was used as the compos mass for the decomposition process. Pellets of three species of Trichoderm i.e T.Koningii (T1), T.reesei (T13) dan T.harzianum (T27) were substituted into the compos at 10th, 20th, 30th days during the decomposition of organic debris by containerizing the treated composes in nylon gauze container and inoculated into the compos mass. At the 70th day the compos were harvest and used as the component of medium to germinate pine seeds. The result show that application of T.koningii increased decomposition base on compos weight by 35,15%, which was lower than control treatment. Application of Trichoderma spp. At 10th day increased the quality of resulted compos compared to those at day 20 and day 30 by 31,09% and 62,18% respectively. Application of T.reesei at day 10 lowered the C-N ratio at the amount of 56,6%. T.koningii showed its biological control potiental at day 10 of application indicated by 60% increased of survival percentage.